Alcohol effects on hepatic lipid metabolism - Jeon, Sookyoung; Carr, Rotonya (Journal of lipid research, 2020)
Alcoholic liver disease (ALD) is the most prevalent type of chronic liver disease with significant morbidity and mortality worldwide. ALD begins with simple hepatic steatosis and progresses to alcoholic steatohepatitis, fibrosis, and cirrhosis. The severity of hepatic steatosis is highly associated with the development of later stages of ALD. This review explores the disturbances of alcohol-induced hepatic lipid metabolism through altered hepatic lipid uptake, de novo lipid synthesis, fatty acid oxidation, hepatic lipid export, and lipid droplet formation and catabolism. In addition, we review emerging data on the contributions of genetics and bioactive lipid metabolism in alcohol-induced hepatic lipid accumulation.